2018
DOI: 10.1556/2006.7.2018.132
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and history of suicide attempts in treatment-seeking patients with gambling disorder: The role of emotion dysregulation and high trait impulsivity

Abstract: Background and aimsGambling disorder (GD) presents high rates of suicidality. The combined influences of emotion dysregulation and trait impulsivity are crucially important (albeit understudied) for developing strategies to treat GD and prevent suicide attempts. The aim of this study is to investigate the association between trait impulsivity, emotion dysregulation, and the dispositional use of emotion regulation (ER) strategies with suicidal ideation and psychopathological symptom severity in GD.MethodsThe sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
4
16
0
2
Order By: Relevance
“…Also, Potenza et al reported that in subjects calling a gambling telephone helpline, individuals also reporting alcohol problems were more likely to report a history of suicide attempts ( 16 ). Further, in some research assessing suicidal behavior in problem gamblers, alcohol and drug use either have not been studied at the same time ( 17 ), or, as in a Spanish clinical study of gambling disorder patients, scores of alcohol and drug problems did not differ significantly between patients with or without a history of suicide attempts ( 18 ). In a study comparing suicide attempts among treatment seeking patients with gambling or substance use disorders, comparable rates of suicide attempts were seen in the groups, although few study participants were diagnosed with both a gambling disorder and a substance use disorder ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Potenza et al reported that in subjects calling a gambling telephone helpline, individuals also reporting alcohol problems were more likely to report a history of suicide attempts ( 16 ). Further, in some research assessing suicidal behavior in problem gamblers, alcohol and drug use either have not been studied at the same time ( 17 ), or, as in a Spanish clinical study of gambling disorder patients, scores of alcohol and drug problems did not differ significantly between patients with or without a history of suicide attempts ( 18 ). In a study comparing suicide attempts among treatment seeking patients with gambling or substance use disorders, comparable rates of suicide attempts were seen in the groups, although few study participants were diagnosed with both a gambling disorder and a substance use disorder ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the heterogeneity of RTBs stems from the variability in their possible combinations (Ahmadi et al 2017;Dougherty et al 2015). Associations between RTBs and SBs are largely documented in gambling (for more recent works, see Bischof et al 2016;Cook et al 2015;Mallorquí-Bagué et al 2018;Moghaddam et al 2015), binge drinking (Byeon et al 2018;Husky et al 2013), risky sexual behavior (Eaton et al 2011;Epstein and Spirito 2010;Houck et al 2008;Husky et al 2013;Thullen et al 2016), dangerous driving behavior (Holland et al 2014;Patel and Luckstead 2000), and extreme sport activities (Tofler et al 2018). Nevertheless, interplays between RTBs, SB, and SUDs remain unclear.…”
mentioning
confidence: 99%
“…Impaired inhibition translates into impulsive behaviours that are strongly associated with suicidal behaviours, especially when violent means are used (Cáceda et al, 2014; Lynam, Miller, Miller, Bornovalova, & Lejuez, 2011; Mallorquí‐Bagué et al, 2018; Swann et al, 2005). Impulsivity is defined as a combination of lack of premeditation and perseverance, sensation‐seeking, and urgency (Whiteside, Lynam, Miller, & Reynolds, 2005).…”
Section: Methodsmentioning
confidence: 99%